Опыт описания кулинарной фразеологии в норвежском и русском языке (Russian and Norwegian culinary expressions) - Komarova, Olga (Poljarnyj vestnik, 2008)
This article presents a description of culinary terms in Russian and Norwegian, and deals with the contrastive study of metaphorical expressions containing such terms, making a special point of their origin, thematic variety and linguistic properties. The author argues that the universal character of metaphorical changes makes itself evident in a large number of expressions containing either verbs connected with cooking or naming products and dishes used as characteristics of a human being or human actions, great number of them being used pejoratively. The author argues that the study of the structure and semantics of these phraseological units can also be of great help in getting a better command of the culture and history of the country and its language.